The Theology of Death in Cantata BMV 106 by J.S Bach: A Critical Study - Yakub Kartawidjaja (Reformed Center for Religion and Society, 2015)
ABSTRACT: The text of Cantata BWV 106 shows two forms of organization: symmetry and chronology. The former is shown by similar sets of correspondences in the musical texture, which display the antithesis: death under the Law versus death under the Gospel. The latter is visible in the four solos and central fugue/solo/chorale complex between the prologue and doxology. The chronology passes through the stages of the history of Israel to the coming of Christ, his death on the cross, and the era of the Christian church. The sequence can be read as an internal progression from fear of death and acceptance of its inevitability to faith in Christ and in the promise of the Gospel, and finally, to the willingness of the believer to die in Christ and his church. KEYWORDS: Luther, death, law, gospel, faith, sleep.